Dietary intake, antioxidants, minerals and vitamins in relation to childhood asthma: a Mendelian randomization study - Luo, Liang; Chen, Guanglei; Zhou, Yan; Xiang, YaJun; Peng, Jing (Frontiers in Nutrition, 2024)
Background Currently, there is limited and inconsistent evidence regarding the risk association between daily dietary intake, antioxidants, minerals, and vitamins with Childhood Asthma (CA). Therefore, this study employs Mendelian Randomization (MR) methodology to systematically investigate the causal relationships between daily dietary intake, serum antioxidants, serum minerals, and the circulating levels of serum vitamins with CA. Methods This study selected factors related to daily dietary intake, including carbohydrates, proteins, fats, and sugars, as well as serum antioxidant levels (lycopene, uric acid, and β-carotene), minerals (calcium, copper, selenium, zinc, iron, phosphorus, and magnesium), and vitamins (vitamin A, vitamin B6, folate, vitamin B12, vitamin C, vitamin D, and vitamin E), using them as Instrumental Variables (IVs). Genetic data related to CA were obtained from the FinnGen and GWAS Catalog databases, with the primary analytical methods being Inverse Variance Weighting (IVW) and sensitivity analysis. Results Following MR analysis, it is observed that sugar intake (OR: 0.71, 95% CI: 0.55–0.91, P: 0.01) is inversely correlated with the risk of CA, while the intake of serum circulating magnesium levels (OR: 1.63, 95% CI: 1.06–2.53, P: 0.03), fats (OR: 1.44, 95% CI: 1.06–1.95, P: 0.02), and serum vitamin D levels (OR: 1.14, 95% CI: 1.04–1.25, P: 0.02) are positively associated with an increased risk of CA. Conclusion This study identified a causal relationship between the daily dietary intake of sugars and fats, as well as the magnesium and vitamin D levels in serum, and the occurrence of CA. However, further in-depth research is warranted to elucidate the specific mechanisms underlying these associations.